Rapid temperature rise may have triggered glacier surges all over Svalbard - Schytt Holmlund, Erik (UiT Norges arktiske universitet, 2020)
Observational and geomorphological records suggest that most glaciers on Svalbard reached their maximum Little Ice Age extents by means of surging. Furthermore, it seems to have happened within just a few decades, suggesting that the rapid concurrent changes in climate might have triggered this widespread surging. The specific precipitation and temperature range of Svalbard seems optimal for glacier surges, and areas with a climatic trend toward the same range may therefore exhibit more glacier surging in the future. This is important, as surges contribute significantly to overall melt and sea-level rise when they occur, and the potential for it to spread is essential to study further. To understand the phenomenon better, five glaciers in Bolterdalen and Foxdalen on Svalbard were studied in depth. Observational, geomorphological, photogrammetric, and ground penetrating radar data indicate that four out of five glaciers seemed to have surged between 1896 and 1936. On average, they lost 81%±7% of their volumes between 1936 and 2019, twice as much as the one glacier that did not show signs of surging. In addition, the glacier Scott Turnerbreen lost 90.4%±5.4 of its volume in the same interval, in a previously undescribed kind of surge where it did not terminate in stagnation directly, but instead continued to advance for many years. This surge and post-surge advance phase occurred over between 22 and 47 years, making it the longest dynamically driven advance ever recorded on Svalbard. The results indicate that climate change-triggered surging may expedite subsequent melt by multiple times, highlighting the immense need to study the phenomenon further and include it in future ice-loss projections.